GAMBARAN KEBUGARAN KARDIORESPIRASI PADA ANAK USIA 10-12 TAHUN DI SEKOLAH DASAR MUHAMMADIYAH 04 DEPOK - Tia Rahmawati (2022)
Children in elementary school need a fit body condition when carrying out daily activities to be able to interact socially, do assignments, and have the spirit of achievement. However, the times have changed the life habits of active children to be replaced with passive activities so that one of the components of physical fitness that is affected is cardiorespiratory fitness. Poor cardiorespiratory fitness can make children more prone to fatigue and a major source of cardiovascular disease. This study will provide an overview of cardiopulmonary fitness in children aged 10-12 years at Muhammadiyah 04 elementary school, Depok. This research is a quantitative descriptive analysis with a cross sectional approach. The population of this study were students at Muhammadiyah 04 Depok elementary school aged 10-12 years with a total sample of 52 students. The parameter is that the Harvard Step Test is useful for measuring physical endurance, especially cardiorespiratory fitness in taking the maximum oxygen volume (VO2Max). The results of this study showed that 52 students had very poor cardiorespiratory fitness (59.6%), poor cardiorespiratory fitness (23.1%), (7.7%) had moderate cardiorespiratory fitness (average), (3.8%) had good cardiorespiratory fitness , and (5.8%) had excellent cardiorespiratory fitness.